LA POLICE VUE D'EN BAS! UNE ETHNOGRAPHIE DES REPRESENTATIONS SOCIALES DE LA POLICE BENINOISE - NANGBE, FLORENTIN; MEHINTO, M. MICHEL (My University, 2015)
Abstract: Of mixed nature and privileging an empirico-inductive approach, this work aims at analyzing the social representations of the policeman in Benin. It is relying on a data collection carried out among police services users, detective division of the French police force, and resourceful persons (Police superintendents, judges, magistrates, etc.) by using an interview guide, direct observation and a questionnaire. The results after analysis show that the population has a quite accurate knowledge of the role and mission of the police. The description done of it, is decidedly close to the normative prescriptions of the domain. It gives an account, explicitly, of both protective and repressive mission of police institution. The complementarity between those two variants, being accepted with difficulty by the citizens who rather put them into opposing relationship leading to a duality of the role of the policeman. The latter protects and represses; a repression that, in the collective social imagination, sounds like abuse. Following the daily functioning of police, the population draws a map of the ideal policeman cantoned in a virtuous style sustained with vocational motivations, imprint of integrity, impartiality, devotion to work, and a surge of sacrifice. That stereotype breaks with the image of the vicious policeman who is racked by cupidity, aggression and “unjustified” violence against citizens. He should not in every respect be ready for illegal negotiations to optimize his personal ambitions generally in discrepancy with the institution objectives. However, what appears paradoxical is that those behavioural deviances of the policeman are constantly encompassed both in the standardization style, the denunciation and complicity. This proves to be only one of the consequences of the functioning difficulties of police Offices: low budget, lack of human, material and security equipment resources, etc. Keywords: Police, social representations, role and mission, virtuous/vicious policeman; Cotonou
Keywords: POLICE; SOCIAL REPRESENTATIONS; COTONOU